You Must Be Joking! Benign Violations, Power Asymmetry, and Humor in a Broader Social Context - Kant, Leo; Norman, Elisabeth (Frontiers in Psychology, 2019)
Violated expectations can indeed be funny, as is acknowledged by incongruity theories of humor. According to the Benign Violation Theory (BVT), something is perceived as humorous when it hits the "sweet spot", where there is not only a violation, but where the violation is also perceived as benign. The BVT specifies how psychological distance plays a central role in determining whether a certain event, joke, or other stimulus is perceived as benign or malignant. In line with the aims of this Research Topic, we specifically address how this "sweet spot" may be influenced by social distance. This form of psychological distance has so far received less attention in the BVT than other forms of distance. First, we argue that the BVT needs to distinguish between different perspectives in a given situation, i.e., between the joke-teller and the joke-listener, and needs to account for the psychological distance between the two parties as well as between each of them and the joke. Second, we argue that the BVT needs to acknowledge possible power asymmetries between the two parties, and how asymmetries might influence the social distance between the joke-teller and joke-listener, as well as between each of these and the joke. Based on the assumption that power influences psychological distance, we argue that power asymmetry may explain certain disagreements over whether something is funny. Third, we suggest that cultural differences might influence shared perspectives on what is benign vs. malignant, as well as power balance. Thus, cultural differences might have both a direct and an indirect influence on what is perceived as humorous. Finally, we discuss potential implications beyond humor, to other social situations with border zones. Close to the border, there is often disagreement concerning attempted violations of expectations and norms, and concerning their nature as benign or malign. This can for instance occur in sexual harassment, #MeToo, bullying, aggression, abusive supervision, destructive leadership, counterproductive work behavior, organizational citizenship behavior, parenting, and family relations. New understanding of border zones may thus be gained from BVT along with our proposed systematically mismatched judgements which parties could make about attempted benign violations.